Concerted Proton-Electron Transfer in the Oxidation of Hydrogen-Bonded Phenols - Rhile, Ian J. (2006)
Three phenols with pendant, hydrogen-bonded bases (HOAr-B) have been oxidized in MeCN with various one-electron oxidants. The bases are a primary amine (–CPh(2)NH(2)), an imidazole, and a pyridine. The product of chemical and quasi-reversible electrochemical oxidations in each case is the phenoxyl radical in which the phenolic proton has transferred to the base, (•)OAr-BH(+), a proton-coupled electron transfer (PCET) process. The redox potentials for these oxidations are lower than other phenols, predominately from the driving force for proton movement. One-electron oxidation of the phenols occurs by a concerted proton-electron transfer (CPET) mechanism, based on thermochemical arguments, isotope effects, and ΔΔG(‡)/ΔΔG°. The data rule out stepwise paths involving initial electron transfer to form the phenol radical cations [(•+)HOAr-B] or initial proton transfer to give the zwitterions [(−)OAr-BH(+)]. The rate constant for heterogeneous electron transfer from HOAr-NH(2) to a platinum electrode has been derived from electrochemical measurements. For oxidations of HOAr-NH(2), the dependence of the solution rate constants on driving force, on temperature, and on the nature of the oxidant, and the correspondence between the homogeneous and heterogeneous rate constants, are all consistent with the application of adiabatic Marcus Theory. The CPET reorganization energies, λ = 23 – 56 kcal mol(−1), are large in comparison with those for electron transfer reactions of aromatic compounds. The reactions are not highly nonadiabatic, based on minimum values of H(rp) derived from the temperature dependence of the rate constants. These are among the first detailed analyses of CPET reactions where the proton and electron move to different sites.